IMPROVING STUDENTS’ ABILITY TO WRITE NARRATIVE TEXT BY USING GRAPHIC ORGANIZER - Resty Maya Sari; Wisma Yunita; Azwandi . (Universitas Bengkulu, 2016)
This paper was aimed to explain whether using Graphic Organizer can improve students’ ability in writing narrative text and factors that influence the improvement of students’ ability at grade IX A of SMPN 22 Kota Bengkulu in the 2012/2013 academic year. The result of this research shows that using graphic organizer has successfully improved the students’ ability in writing narrative text, the improvement was influenced by the used of interesting material chosen and teacher’s participation toward the students